MDCKE: Multimodal deep-context knowledge extractor that integrates contextual information - Hyojin Ko; Joon Yoo; Ok-Ran Jeong (Alexandria Engineering Journal)
Extraction of comprehensive information from diverse data sources remains a significant challenge in contemporary research. Although multimodal Named Entity Recognition (NER) and Relation Extraction (RE) tasks have garnered significant attention, existing methods often focus on surface-level information, underutilizing the potential depth of the available data. To address this issue, this study introduces a Multimodal Deep-Context Knowledge Extractor (MDCKE) that generates hierarchical multi-scale images and captions from original images. These connectors between image and text enhance information extraction by integrating more complex data relationships and contexts to build a multimodal knowledge graph. Captioning precedes feature extraction, leveraging semantic descriptions to align global and local image features and enhance inter- and intramodality alignment. Experimental validation on the Twitter2015 and Multimodal Neural Relation Extraction (MNRE) datasets demonstrated the novelty and accuracy of MDCKE, resulting in an improvement in the F1-score by up to 5.83% and 26.26%, respectively, compared to State-Of-The-Art (SOTA) models. MDCKE was compared with top models, case studies, and simulations in low-resource settings, proving its flexibility and efficacy. An ablation study further corroborated the contribution of each component, resulting in an approximately 6% enhancement in the F1-score across the datasets.